APLIKASI SISTEM INFORMASI GEOGRAFIS DALAM PENENTUAN DAERAH PENGOPERASIAN ALAT TANGKAP GOMBANG DI PERAIRAN SELAT BENGKALIS KECAMATAN BENGKALIS KABUPATEN BENGKALIS PROPINSI RIAU - Syofyan, Irwandy; Jhonerie, Rommie; AR, Kasman (Jurnal Perikanan dan Kelautan, 2009)
This research was conducted on December 2008 to January 2009 atMalacca strait waters. Purpose of this research to determine potential coastal zonefor stow net fishing ground. This research was used survey method, which toobserve and measure fishing ground parameters, such as current speed, depth andwater transparency. All of the data was analyzed descriptively, which discussedsystematically on the study location. At every parameter data was analyzed byGIS technology spatially with overlay index model method. Based on the dataanalyzed can determine the potential fishing ground as very potential, potentialand impotential.